Muscle injuries: optimising recovery - Järvinen, Tero A.H., MD, PhD; Järvinen, Teppo L.N; Kääriäinen, Minna; Äärimaa, Ville; Vaittinen, Samuli; Kalimo, Hannu; Järvinen, Markku (Best practice & research. Clinical rheumatology, 2007)
Muscle injuries are one of the most common traumas occurring in sports. Despite their clinical importance, there are only a few clinical studies on the treatment of muscle injuries. Lack of clinical studies is most probably attributable to the fact that there is not only a high heterogeneity in the severity of injuries, but also the injuries take place in different muscles, making it very demanding to carry out clinical trials. Accordingly, the current treatment principles of muscle injuries have either been derived from experimental studies or been tested empirically only. Clinically, first aid for muscle injuries follows the RICE (Rest, Ice, Compression and Elevation) principle. The objective of RICE is to stop the injury-induced bleeding into the muscle tissue and thereby minimise the extent of the injury. Clinical examination should be carried out immediately after the injury and 5–7 days after the initial trauma, at which point the severity of the injury can be assessed more reliably. At that time, a more detailed characterisation of the injury can be made using imaging diagnostic modalities (ultrasound or MRI) if desired. The treatment of injured skeletal muscle should be carried out by immediate immobilisation of the injured muscle (clinically, relative immobility/avoidance of muscle contractions). However, the duration of immobilisation should be limited to a period sufficient to produce a scar of sufficient strength to bear the forces induced by remobilisation without re-rupture and the return to activity (mobilisation) should then be started gradually within the limits of pain. Early return to activity is needed to optimise the regeneration of healing muscle and recovery of the flexibility and strength of the injured skeletal muscle to pre-injury levels. The rehabilitation programme should be built around progressive agility and trunk stabilisation exercises, as these exercises seem to yield better outcome for injured skeletal muscle than programmes based exclusively on stretching and strengthening of the injured muscle.